Spatial disparities in productivity and industry mix: The case of the European regions - Juan Miguel Benito; Roberto Ezcurra (European Regional Science Association (ERSA), 2004)
This paper applies nonparametric techniques in order to examine the evolution of the entire distribution of regional productivity in the European Union between 1977 and 1999. Likewise, we study the strength of the respective roles played by regional and sectoral factors in the convergence in productivity observed in the European context. To achieve this aim, we consider a new methodology involving a modification of conventional shift-share analysis and various results reported in the literature on personal income distribution. Our results suggest that regional inequality in productivity in the European Union is closely linked to intrinsic differences between regions. Likewise, the analyses performed reveal the major role played by the national component and the spatial dimension in the explanation of regional disparities in the product per worker in the European Union. In addition, our findings support the relevance of one-sector growth models for analysing regional disparities in per capita income.
Keywords: 330